EFFECT OF ADVERSITY QUOTIENT ON STUDENTS’ ACADEMIC PERFORMANCE IN PUBLIC AND PRIVATE UNIVERSITIES (Qualitative Research Journal for Social Studies, 2026)
The current study aimed at assessing how Adversity Quotient (AQ) affects the academic performance of students among university students in both public and private universities. AQ is the capability of an individual to handle stressors, surmount hardships and convert hardships into opportunities. The quantitative research design used was causal-comparative and data was gathered using a random sampling technique on a sample of 400 students selected in two public universities and two private universities in Lahore. The measures of AQ and academic performance were measured using standardized questionnaires and the data were analyzed using both descriptive statistics and inferential statistics in SPSS. The results indicated a huge difference in academic performance at different levels of AQ, meaning that students with higher levels of AQ had better academic performance. According to AQ or academic performance, there were no significant gender differences. Likewise, there was no meaningful difference between the students at public university and the students at the private university or even among the institutions. Nevertheless, there was a great discrepancy between urban and rural students with the urban students doing well. The difference in academic performance across academic programs also exhibited significant differences whereas there was no significant difference in transportation method. Parental education, especially the level of mother education, had a significant direct effect on the academic performance but family income did not have any direct effects. The research finds that AQ is a significant indicator of academic performance and has a crucial role in student success. The findings point to the need to come up with resilience-building interventions in learning institutions to improve academic results and promote student success.